(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
There are 73 species of fish in the water bodies of Uzbekistan, of which only 35 species are considered commercial (48%) and the remaining 38 species (52%) are considered less valuable or weedy. Of the 35 species of commercial fish, about 18-20 species are caught for commercial purposes, others have smaller populations, and some are listed in the Red Book.